2014
DOI: 10.1002/jcb.24857
|View full text |Cite
|
Sign up to set email alerts
|

A phenolic acid phenethyl urea derivative protects against irradiation-induced osteoblast damage by modulating intracellular redoxstate

Abstract: Because irradiation may cause osteoradionecrosis, antioxidant supplementation is often used to suppress irradiation-mediated injury. This study examined whether a synthetic phenethyl urea compound, (E)-1-(3,4-dihydroxyphenethyl)-3-(3,4-dihydroxystyryl)urea (DPDS-U), prevents irradiation-mediated cellular damage in MC3T3-E1 osteoblastic cells. A relatively high dose of irradiation (>4 Gy) decreased cell viability and proliferation and induced DNA damage and cell cycle arrest at the G(2)/M phase with the attenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…We previously found that Nrf2-mediated signaling could play dual roles on the viability of cells depending on the condition of stress exposed; under a mild oxidative stress, Nrf2 activation has a protective role by maintaining normal levels of ROS, whereas it leads to cell injury under a persistent oxidative stress (20) . However, the current results highlight that activation of the Nrf2 pathway by H 2 O 2 contributes predominantly to the down-regulation of microenvironmental events required for osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that Nrf2-mediated signaling could play dual roles on the viability of cells depending on the condition of stress exposed; under a mild oxidative stress, Nrf2 activation has a protective role by maintaining normal levels of ROS, whereas it leads to cell injury under a persistent oxidative stress (20) . However, the current results highlight that activation of the Nrf2 pathway by H 2 O 2 contributes predominantly to the down-regulation of microenvironmental events required for osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, oxidative stress induces translocation of Nrf2 into the nucleus, in which Nrf2 stimulates transcriptional activation of redoxsensitive target genes such as CAT and SOD. It has also been reported that the induction of Nrf2 protects against oxidative-stress-induced DNA damages (23). Therefore, it is hypothesized that irradiationmediated accumulation of intracellular ROS activates the Nrf2 signal, and this activation positively controls cellular homeostasis and redox balance.…”
mentioning
confidence: 97%
“…Although others [ 52 , 53 ] have shown the beneficial effects of various antioxidants to confer radioprotection for various osteoblast cell lines, we show here a direct comparison of antioxidant treatment with different radiation species when added to primary, marrow-derived osteoprogenitors. Interestingly, adding SOD at higher doses or for longer periods was not advantageous, emphasizing the importance of carefully titrating radical scavengers such as SOD, possibly to maintain endogenous ROS-dependent signalling.…”
Section: Discussionmentioning
confidence: 82%